Peningkatan Kompetensi Kearsipan Bagi Guru dan Siswa SMK Marisi Medan - Mutmainnah, Sri; Simanullang, Rotua Sahat Pardamean; Sitanggang, Gartima; Pramana, Dodi (Yayasan Cita Cendikiawan Al Kharizmi, 2023)
The purpose of this dedication activity is to increase the competence of Archives Teachers at the Marisi Private Vocational High School Medan in overcoming some of the problems being faced. This problem arises because most of the Archives teachers in the Department of Office Administration are not graduates of Office Administration Education which results in a lack of mastery of archival material. So it is necessary to conduct training in order to strengthen the Professional competence of Archives teachers at Marisi Private Vocational High School Medan. The specific target of this dedication activity is the increasing professional competence in the field of Archives for teachers and students of Office Administration at Marisi Private Vocational High School Medan. The professional competencies that are trained for teachers are: 1) Storage procedures; 2) Use and maintenance of archives; 3) Determination of archive retention period; 4) Depreciation of archives; 5) Electronic/digital archive management.